Pengaruh penambahan simplisia jahe merah (Zingiber Officinale Var Rubrum Rhizoma) terhadap sifat kimia dan organoleptik teh daun kelor (Moringa Oleifera) - Riski Bayu Lintang; Nurul Hidayah (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2024)
Tea is a drink that is much sought after by Indonesian people. Moringa leaves have a high antioxidant content, especially flavonoids and polyphenols which can be used as raw materials for tea. Red ginger is a type of rhizome that is rich in phenolic compounds and essential oils. Red ginger in simplicia form is added to tea to improve the organoleptic properties and increase the antioxidant activity of Moringa leaf tea. The aim of this research was to determine the effect of adding red ginger simplicia on the chemical and organoleptic properties of Moringa leaf tea. This research used a Completely Randomized Design (CRD) and was repeated 3 times consisting of 5 treatments with the addition of red ginger simplicia, namely P1 (0%), P2 (10%), P3 (20%), P4 (30%), and P5 (40%). The resulting data was analyzed using One Way ANOVA with a significance level of 5% with the DMRT (Duncan's Multiple Range Test) further test. Test parameters include water content, ash content, flavonoids, antioxidants, polyphenols, tannins and organoleptics. Organoleptic tests with a total of 30 panelists include color, aroma, taste, aftertaste and overall. The highest value is found in P5 with antioxidant activity IC50Â of 33.86 ppm, polyphenols of 59.94 mgGAE/g, flavonoids of 87.14 mgQE/g, P5 tannins of 50.81 mgCE/g, and organoleptic results that are preferred by consumers overall it is P4 with a value of 3.90. The results of this study showed that the addition of red ginger simplicia had an effect on the test parameters for water content, ash content, polyphenols, flavonoids, tannins and organoleptics of Moringa leaf tea.